Biological technology and agricultural policy: an assessment of azolla in Philippine rice production - Rosegrant, Mark W.; Roumasset, James A.; Balisacan, Arsenio, M. (Wiley, 1985)
Concerns about external debt and energy security have motivated several developing countries to develop biological technologies to substitute for petrochemical inputs. This paper examines the economic feasibility of azolla as a source of nitrogen in Philippine rice production. Green manuring with azolla is found not to be cost effective. Substantial savings from intercropping with azolla can be realized only if the cost of nitrogen from azolla is compared with the price of nitrogen from ammonium sulfate, but not if urea is used as the basis of comparison. Farmers would benefit more from liberalization of import controls on urea. Additional research is needed to develop appropriate chemical‐saving systems before investing heavily in extension.